What's said in a subject line? Framing the email subject lines in health messages sent to university students - Miller, Alison K.; Rothman, Alexander J.; Lenne, Richie L. (Journal of American college health, 2022)
Objective To examine whether manipulating the frame used in email subject lines affects open or click-through rate. Participants: Students (N = 38,538) at a Midwestern university received emails from their health clinic about a stress management program (September - December 2017). Method: Three subject lines (Action Instruction only, Gain Frame plus Action Instruction, Non-loss Frame plus Action Instruction) were used. Each student randomly received one subject line in the first two months and one in the next two months. Email open and click-through rates were measured. Results: Emails with the Action Instruction only subject line were more likely to be opened; there was no difference in open rate between the two framed subject lines, and no effect on click-through rates. Conclusion: This study supports the benefits of action instructions to encourage behavior change but calls for further research on the effects of frames and action instructions in email subject lines.